COMPARISON OF PHYTOCHEMICALS AND ANTIOXIDANT CAPACITY OF HYPERICUM PERFORATUM; WILD PLANT PARTS AND IN VITRO SAMPLES - C. Yaman 1; Ş. Önlü; H. A. A. Ahmed; R. Erenler (Journal of Animal and Plant Sciences, 2022)
The aim of study is to compare the phytochemicals and free radical scavenging activities in methanol extracts of flower, leaf, stem in vitro plantlet, callus of Hypericum perforatum L. In vitro cultures of H. perforatum was established by using MS-B5 medium contained plant growth regulators such as BAP, TDZ and picloram. Total phenolics and flavonoids were analysed by spectrophotometric methods.The stem was the richest in total phenolics (228.9 mg GAE/g extract) and flavonoids (102.4 mg QE/g extract). Quinic acid, gallic acid, (+)-catechin, ferulic acid, vanillic acid, p-coumaric acid, caffeic acid, and quercetin were determinated by LC-MS/MS. Free radical scavenging activities (ABTS and DPPH) of all samples were detected as IC50 values, and was compared to standards such as trolox and ascorbic acid. As a result, the stem exhibited the stronger antioxidant activities than other samples, and vanillic acid, ferulic acid and gallic acid could be produced by in vitro culture.
Keywords: Hypericum perforatum; antioxidant activity; in vitro plantlets; phytochemicals